2013
DOI: 10.1177/1403494813491859
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adolescents who perceive their parents to have alcohol problems: A Swedish national survey using a web panel

Abstract: These results indicate that the problem is widespread. Our findings are similar to previous research where a more indirect methodology has been adopted, using either psychiatric interviews or self-reported alcohol consumption of adults, to estimate the magnitude of the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 16 publications
(17 reference statements)
2
23
2
Order By: Relevance
“…Moreover, a web-based design guarantees participants anonymity and minimizes the risk for interviewer bias and bias due to fear of negative consequences related to certain answers. Furthermore, public opinion surveys typically suffer from low response rates [39]. A response rate of 68% for the current study increases both the validity and the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, a web-based design guarantees participants anonymity and minimizes the risk for interviewer bias and bias due to fear of negative consequences related to certain answers. Furthermore, public opinion surveys typically suffer from low response rates [39]. A response rate of 68% for the current study increases both the validity and the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 73%
“…In a survey targeting 1000 randomly selected Swedish 16-19-year-olds, about 20 percent of the adolescents were classified as having parents with alcohol problems. Further, 44 percent reported that they think someone close to them drinks too much alcohol and about 22 percent of these responded that this has hurt them or caused them problems (Elgán & Leifman, 2013). The group of youth at risk of alcohol related and other problem behaviours associated with problematic familial use of alcohol is thus of significant size.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, available international estimates suggest that 8-23% of all children have parents with mental health problems [1,2] while 8-30% grow up with at least one parent having alcohol drinking problems [3][4][5]. Estimates in Sweden are in line with these figures [6][7][8], which puts a large proportion of Swedish children at risk for many acute and long-lasting negative consequences such as poor mental health, substance use problems and poorer academic achievement [9][10][11][12][13][14][15]. For instance, parental mental health problems such as mood and anxiety disorder and depression appear to have a high and long-lasting risk for children to develop own depression, somatic morbidity and higher mortality [16,17], which may also be explained by genetic vulnerability [18].…”
Section: Introductionmentioning
confidence: 73%